The Use of Analytic Hierarchy Process (AHP) in the Analysis of Delay Claims in Construction Projects in the UAE - Perera, N.; Sutrisna, Monty (Emerald, 2010)
Central to successful resolution of delay based claims in construction projects is the fair and equitable apportioning of parties’ liabilities. However, such fairness and equity in apportioning may be fettered by many factors in contemporary practices adopted by both contractors and clients in construction industries including in the United Arab Emirates (UAE). The principal goals and rationale of this research are inspired by the need to identify such potentially major obstructive factors and provide improvements to the problematic situations that may stem from them. One such factor in apportioning liabilities is identified in that there is no universally acceptable delay analysis methodology amongst practitioners. As the research study aims to bring about contractually sound, practical improvements to problematic situations in contemporary practices, an area of such improvements is identified in developing a model for selection of most appropriate delay analysis method under a set of specific circumstances of a project. Such model is expected to provide the practitioners with a more objective and tenable basis for delay analysis which would enhance fair and equitable outcome in apportioning liabilities. In building this model, the Analytic Hierarchy Process (AHP) has been selected as the appropriate decision making tool. Despite its reliance on mathematical manipulation, AHP embraces the use of mixed or multiple methods in its data collection and analysis. The interplay between quantitative and qualitative data and analysis is expected to result in the phenomenon of apportioning liabilities in delay claims resolution being seen from different perspectives illuminated with mixed methods.